THE EYE AS AN INTERFACE: HOW XR, AI AND AUTOMATION CHANGED OPHTHALMIC PRACTICE (2015–2025) - Magdalena Fidelis; Maria Wojcieszek; Katarzyna Gondek; Dominika Gacka; Agnieszka Zalewska; Aleksandra Mączyńska; Noor Alhuda Al-karawi; Paulina Kędziorek; Zuzanna Tanç (International Journal of Innovative Technologies in Social Science, 2026)
This review examines the integration of emerging digital technologies in ophthalmology to address global vision impairment affecting over 2.2 billion people, with a focus on scalability, equity, and sustainability amid rising age-related pathologies like AMD, glaucoma, and DR.Objectives: Synthesize evidence from 2015-2025 on xVR/AR, AI, teleophthalmology, robotics, and nanotechnology, evaluating clinical efficacy, economic viability, ethical implications, and environmental impact.Methods: Systematic literature search across PubMed, Scopus, IEEE Xplore, and Web of Science using Boolean keywords for targeted technologies. Inclusion: peer-reviewed studies with quantitative outcomes (e.g., visual acuity, AUC, CO2 reductions); exclusion: pre-2015, non-English, non-clinically validated works. Data extraction emphasized study design, interventions, outcomes, biases, and ethics.Key Findings: VR dichoptic therapy yields 1.8 logMAR improvements in amblyopia with 88% adherence, surpassing patching. AI achieves >90% sensitivity for DR screening, mitigated by generative models for bias. Teleophthalmology resolves 75% cases remotely, saving up to 176 kg CO2/patient. Robotics enable 5%); 3D bioprinting pioneers corneal implants.Conclusions: These technologies foster precise, decentralized eye care, but require addressing biases, regulations, and access barriers for equitable global impact.